A New Diagnostic Model to Distinguish Kawasaki Disease From Other Febrile Illnesses in Chongqing: A Retrospective Study on 10,367 Patients - Huang, Zhilin; Tan, Xu-Hai; Wang, Haolin; Pan, Bo; Lv, Tie-Wei; Tian, Jie (Frontiers in Pediatrics, 2020)
Objective: Kawasaki disease (KD) is one of the most prevailing vasculitides among infants and young children and has become the leading cause of acquired heart disease in childhood. Delayed diagnosis of KD may cause serious cardiovascular complications. We sought to create a diagnostic model to aid in distinguishing subjects with KD from febrile controls (FCs) to allow prompt treatment. Methods: Data were retrospectively collected and compared between KD group and FCs group. The independent risk factors were identified applying multivariate regression analysis. A new diagnostic model was constructed and compared with the previous diagnostic test. Results: A total of 10367 patients were collected and twelve independent risk factors were determined including lower percentage of monocyte(P-MON), lower phosphorus, lower uric acid (UA), higher globulin, lower percentage of lymphocyte (p-LYM), lower prealbumin, higher gamma-glutamyl transpeptidase(GGT), lower AST/ALT, lower serum chlorine, lower lactic dehydrogenase(LDH), higher platelet count (PLT) and younger age. The AUC, sensitivity and specificity of the new diagnostic model for the cross-validation of KD diagnosis were 0.906±0.006, 86.0±0.9%, and 80.5±1.5%, respectively. An equation is presented to assess the risk of KD which was further validated using both KD (n=5642) and incomplete KD (n=809) cohort. Conclusions: patients with KD could be effectively distinguished from other febrile diseases by P-MON, phosphorus, UA, globulin, P-LYM, prealbumin, GGT, AST/ALT, serum chlorine, LDH, PLT and age. The new diagnostic model might provide better evidence for accurately diagnosis of KD.